Effects of plyometric training on kicking performance in soccer players: A systematic review and meta-analysis - Zhang, Y.; Li, D.; Gómez-Ruano, M. Á.; Memmert, D.; Li, C.; Fu, M. (Frontiers in Physiology, 2023)
This systematic review and meta-analysis aimed to determine the pooled effect size (ES) of plyometric training (PT) on kicking performance (kicking speed and distance) in soccer players depending upon some related factors (i.e., age, gender, skill level, and intervention duration). This study was carried out according to the PRISMA guidelines. Four electronic databases—EBSCO, PubMed, Scopus, and Web of Science—were searched for relevant studies. A total of n = 16 studies yielding 17 ES with n = 553 participants were finally included in the meta-analysis. A random-effects model was used to calculate Hedge`s g with a 95% confidence interval (CI), which showed that plyometric training had a large-sized positive effect on soccer kicking performance (g = 0.979, 95% CI [0.606, 1.353], p < 0.001). Subgroup analyses were performed according to participants` characteristics (i.e., age, gender, skill level) and intervention duration, demonstrating no significant differences between these subgroups. The study pointed out that plyometric training is a generally effective method to improve soccer players` kicking performance, which plays a crucial role in passing and shooting actions during games. As for soccer players and strength and conditioning coaches, the plyometric training aiming to enhance kicking performance has valuable implications in practice. Therefore, besides well-known training methods like power training in the weight room, plyometric training could be incorporated into the overall strength and conditioning programs for soccer players to reach high standards of kicking performance.